A PLEA FOR RETHINKING INSTITUTIONAL LANGUAGE POLICY DOCUMENTS - PĂCURAR, Elena (Studia Universitatis Babeș-Bolyai Philologia, 2019)
A Plea for Rethinking Institutional Language Policy Documents. The present study aims to raise awareness on and to provide a synopsis of the role, function and relevance of language policy documents in HE, by bringing together some of the more recent conclusions of strategic papers or guidelines issued by representative bodies responsible for the standardization of language teaching and testing. The current definitions of and views on language policies invite reflections on the margins of the internationalisation of HE, the digitalisation of education and its tools, the role of the language instructors in the 21st century and, last but not least, the existence of institutional strategic documents. A local case (the language policy at Babeș-Bolyai University) is discussed against the backdrop of international frameworks for language instruction and in comparison with similar (national) language policies. Rezumat. O pledoarie pentru regândirea documentelor de politică lingvistică la nivel instituțional. Studiul de față își propune să atragă atenția asupra rolului, funcției și relevanței documentelor de politică lingvistică din învățămîntul superior prin scurta trecere în revistă a unor concluzii ce rezultă din câteva ghiduri sau cadre normative elaborate recent de către instituții a căror misiune asumată este standardizarea predării și învățării limbilor. Definițiile și perspectivele actuale asupra politicilor lingvistice discută și aspecte legate de internaționalizarea învățământului superior, digitalizarea educației și a instrumentelor aferente, rolul instructorilor de limbă în secolul al XXI-lea, precum și existența unor documente strategice la nivel instituțional. Acest articol introductiv mai include și un studiu de caz local (documentul de politică lingvistică elaborat de Universitatea Babeș-Bolyai) revăzut din perspectiva unor modele-cadru privind instruirea lingvistică existente la nivel național sau internațional. Cuvinte-cheie: politică lingvistică, standardizare, instruire lingvistică, internaționalizarea învățămîntului superior, abilități pentru secolul al XXI-lea.